Internet et ses espaces : vers une économie politique de la production urbaine par les centres de données - Émile Pronovost; Julia Frotey; Morgan Mouton (Netcom)
Ever since the early development of the Internet, scholars in urban studies and geography have sought to examine the infrastructures that subtend the development of this new telecommunication network. A first wave of research on the material dimension of information technologies brought precious insights into their relationship with urban production. Today, the ever-expanding reach of digitalization and the massification of data production, collection, processing and storage have prompted a second wave of scholarship on digital infrastructures. In particular, the rise of large, “hyperscale” data centers has triggered the publication of considerable literature that explores how these facilities relate to their surrounding space, resources, and communities. This paper presents a review of the social science literature on the material dimension of data centers and on their place in dynamics of urban production, in the age of digital capitalism.